Responses of coffee farming households during the first wave of Covid-19 in western Honduras - Rodríguez Camayo, Fernando; Lundy, Mark M.; Borgemeister, Christian; Beuchelt, Tina (2022)
This is a structured household survey of coffee farming households from Ocotepeque, western Honduras. Data collection took place in July 2020. The main national curfew was imposed on March 15–31, 2020, and mobility restrictions within municipalities and between municipalities and states were implemented from April 1 to September 2020. This survey builds on a previous, more extensive, household survey that was conducted in 2019, pre-Covid-19. The two cooperatives and households selected for the survey in 2020 represented a subsample of those surveyed in 2019.